Palaeobiology of red and white blood cell-like structures, collagen and cholesterol in an ichthyosaur bone. Issue 1 (December 2017) - Plet, Chloé; Grice, Kliti; Pagès, Anais; Verrall, Michael; Coolen, Marco; Ruebsam, Wolfgang; Rickard, William; Schwark, Lorenz
Abstract Carbonate concretions are known to contain well-preserved fossils and soft tissues. Recently, biomolecules (e .g . cholesterol) and molecular fossils (biomarkers) were also discovered in a 380 million-year-old concretion, revealing their importance in exceptional preservation of biosignatures. Here, we used a range of microanalytical techniques, biomarkers and compound specific isotope analyses to report the presence of red and white blood cell-like structures as well as platelet-like structures, collagen and cholesterol in an ichthyosaur bone encapsulated in a carbonate concretion from the Early Jurassic ( 182.7 Ma). The red blood cell-like structures are four to five times smaller than those identified in modern organisms. Transmission electron microscopy (TEM) analysis revealed that the red blood cell-like structures are organic in composition. We propose that the small size of the blood cell-like structures results from an evolutionary adaptation to the prolonged low oxygen atmospheric levels prevailing during the 70 Ma when ichthyosaurs thrived. The δ13 C of the ichthyosaur bone cholesterol indicates that it largely derives from a higher level in the food chain and is consistent with a fish and cephalopod diet. The combined findings above demonstrate that carbonate concretions create isolated environments that promote exceptional preservation of fragile tissues and biomolecules.